2021
DOI: 10.1248/bpb.b21-00248
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescein Permeability of the Blood–Brain Barrier Is Enhanced in Juvenile- but Not Young Adult-Onset Type 1 Diabetes in Rats

Abstract: Clinically, neurological disorders, such as cognitive impairments and dementia, have been reported as diabetic complications, which are remarkable, especially in children with diabetes. The blood-brain barrier (BBB) is a physiologically dynamic regulatory barrier that maintains the consistency of the fluid microenvironment composition of the brain. However, the differences in BBB conditions between children and adults and the contribution of the BBB to the severity of cognitive impairments remain unclear. We g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…In type 2 diabetes mellitus model Bio-Breeding Zucker diabetic rat (BBZDR)/Wor rats, it is found that more than 84% of the brain regions show increased BBB permeability, while the cerebellum and midbrain do not change significantly [ 18 ]. In juvenile-onset diabetic rat models, the BBB permeability of hippocampus and striatum increases, but no change is observed in the frontal cortex and hypothalamus [ 19 ]. In a diet-induced obese model of type 2 diabetes mellitus, BBB damage mainly occurs in the hypothalamus and hippocampus [ 20 ].…”
Section: Diabetes Damages Glia and Vascular Cells Of Bbbmentioning
confidence: 99%
“…In type 2 diabetes mellitus model Bio-Breeding Zucker diabetic rat (BBZDR)/Wor rats, it is found that more than 84% of the brain regions show increased BBB permeability, while the cerebellum and midbrain do not change significantly [ 18 ]. In juvenile-onset diabetic rat models, the BBB permeability of hippocampus and striatum increases, but no change is observed in the frontal cortex and hypothalamus [ 19 ]. In a diet-induced obese model of type 2 diabetes mellitus, BBB damage mainly occurs in the hypothalamus and hippocampus [ 20 ].…”
Section: Diabetes Damages Glia and Vascular Cells Of Bbbmentioning
confidence: 99%